2014
DOI: 10.1158/1078-0432.ccr-13-3157
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence and Clinical Implications of Epstein–Barr Virus Infection in De Novo Diffuse Large B-Cell Lymphoma in Western Countries

Abstract: Purpose Epstein-Barr virus (EBV)-positive diffuse large B-cell lymphoma (DLBCL) of the elderly is a variant of DLBCL with worse outcome that occurs most often in East Asian countries and is uncommon in the Western hemisphere. We studied the largest cohort of EBV+ DLBCL, independent of age, treated with R-CHOP in developed Western countries. Experimental design A large cohort (n=732) of patients with DLBCL treated with R-CHOP chemotherapy are included from the multicenter Consortium. This study group has been… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
167
6
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 126 publications
(197 citation statements)
references
References 42 publications
22
167
6
2
Order By: Relevance
“…In this study, a notable adverse prognostic factor was lymphopenia defined as an absolute lymphocyte count of <1.0 3 10 9 /L. Of potentially clinical implication is the finding that expression of CD30 is not only increased but also associated with a worse OS in patients with EBV-positive DLBCL [16]. In this study, EBER1/CD301 DLBCL patients had worse outcome than EBER1/CD30-or EBER-/CD301 DLBCL patients.…”
Section: Other Prognostic Factorsmentioning
confidence: 51%
See 2 more Smart Citations
“…In this study, a notable adverse prognostic factor was lymphopenia defined as an absolute lymphocyte count of <1.0 3 10 9 /L. Of potentially clinical implication is the finding that expression of CD30 is not only increased but also associated with a worse OS in patients with EBV-positive DLBCL [16]. In this study, EBER1/CD301 DLBCL patients had worse outcome than EBER1/CD30-or EBER-/CD301 DLBCL patients.…”
Section: Other Prognostic Factorsmentioning
confidence: 51%
“…In a multicenter consortium study on DLBCL patients treated uniformly with R-CHOP, the response and survival rates of 28 patients with EBV-positive DLBCL was compared with 695 EBVnegative patients, and showed no statistical differences [16]. Interestingly, there were no differences in clinical presentation between the two groups.…”
Section: Risk Stratificationmentioning
confidence: 97%
See 1 more Smart Citation
“…8 Although several groups have shown NF-κB expression in DLBCL, many of these studies have lacked cutoff values for respective NF-κB proteins or did not study all five subunits. More importantly, they did not specifically exclude cases with infection by Epstein-Barr virus, which is known to activate the NF-κB pathway 26 or had relatively small cohort of patients. 16 In this study, expression of p50, p52, p65, RELB, and c-Rel was observed in 34%, 12%, 20%, 14% and 23% of patients, respectively, and expression of p50/p65, p50/c-Rel and p52/RELB dimers was seen in 11%, 11% and 3% of patients, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Such observation has been found in several former and current publications. 18,21,22,24,[26][27][28] Expression of NF-κB Subunits in DLBCL Nuclear expression with or without cytoplasmic expression of each marker in lymphoma cells was considered positive (Figure 1a). Excluding 36 cases with tissue exhaustion, a total of 278 (56%) cases expressed at least one of NF-κB subunits (Table 1).…”
Section: Patient Characteristicsmentioning
confidence: 99%